Biological and Ethnobotanical Characteristics of Nipa Palm (Nypa fructicans Wurmb.): A Review (Ciri-Ciri Biologi dan Etnobotani Nipah (Nypa fruticans Wurmb.) – Suatu Tinjauan) - Koji Tsuji; Mohd Nor Faizal Ghazalli; Zulhairil Ariffin; Mohd Shukor Nordin; Maya Izar Khaidizar; Mohammad Ehsan Dulloo; Sebastian, Leocadio S. (Universiti Kebangsaan Malaysia, 2011)
Nipa (Nypa fruticans) is one of the most widely distributed and useful palm in the mangrove forests in the South, Southeast Asia and Oceania. Its distribution area is known to be larger in ancient time than at present, as evidenced by its fossils found in North America, South America, Egypt and Europe. Nipa has a wide diversity of use. Traditionally it is used as roof materials, cigarette wrapper, medicine and its sap is fermented to alcohol. Recently, research on nipa has focused on its potential use as a biofuel crop because it has several advantages compared with other biofuel-alcohol crops. For example it has high alcohol content, no competition with other crop for agricultural land and no bagasse disposal problem. In spite of such usefulness, scientific reports on biology of nipa are limited. Information on genetic diversity, cytogenetics and chemical composition are lacking for nipa plant. On the other hand, morphological characters of nipa have been described in many reports. This paper attempted to provide a general review of the nipa plant based on available literatures.